Mary and Fátima A Modest C-Inductive Argument for Catholicism - McNabb, Tyler Dalton ca. 20./21. Jh.; Blado, Joseph E. (2020)
C-Inductive arguments are arguments that increase the probability of a hypothesis. In this paper, we offer a C-Inductive argument for the Roman Catholic hypothesis. We specifically argue that one would expect the Miracle of Fátima on Roman Catholicism more so than on alternative hypotheses. Since our argument draws on confirmation theory, we first give a primer for how confirmation theory works. We then, provide the historical facts surrounding the Miracle of Fátima. We offer up two competing naturalistic explanations that attempt to explain the historical facts, but then, argue that a supernatural explanation is superior. Having established that something miraculous likely occurred at Fátima, we move to argue for the overall thesis of the paper. Finally, we engage several objections to our argument.
Keywords: Swinburne; Miracle of the Sun; Roman Catholicism; Fátima